Sesama Beda Agama (Islam-Kristen) Sebelum dan Sesudah Konflik Sosial di Kota Masohi - Nofry Puttileihalat (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2020)
In the context of religious plurality, interreligious relations need to be positioned within the framework of humanitarian relations, because inter-religious relations which are placed apart from inter-human references result in religion losing its meaning. This article aims to describe the fellowship from the perspective of Christians and Muslims in Masohi. This description is essential because the conflict experiences experienced by the two religious communities in Masohi need to be constructed to build a future of peaceful religions. This study uses a qualitative descriptive approach with the perspective of religious studies. The research concludes that the view of fellowship in the period before and after the conflict in Masohi was that both Christians and Muslims still saw them as brothers and sisters due to cultural bond, pela-gandong.